2020
DOI: 10.1029/2019jd031815
|View full text |Cite
|
Sign up to set email alerts
|

Observation Constrained Aromatic Emissions in Shanghai, China

Abstract: Aromatics in the atmosphere are a large contributor to ozone and secondary organic aerosol formation and have an adverse impact on human health. Observation‐based emissions are urgently needed for air quality management and decision making due to the large uncertainties in the emissions inventories. Atmospheric aromatics were continuously observed at one urban site in Shanghai of China in 2015, which were compared with the simulations of the Community Multiscale Air Quality (CMAQ) model. Large differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…The PM 2.5 composition and VOCs measurements were made at the SAES site, and the measurement methods have been described in previous studies and references therein. 22 25 …”
Section: Methodsmentioning
confidence: 99%
“…The PM 2.5 composition and VOCs measurements were made at the SAES site, and the measurement methods have been described in previous studies and references therein. 22 25 …”
Section: Methodsmentioning
confidence: 99%
“…The maximum emission in July was (17.4 AE 7.7) Gg per month, which was approximately 3.2 times higher than the emission in February ((5.5 AE 2.1) Gg per month). 40 More recently, Han et al also reported obvious seasonal variations of BTEX at a regional background site in Fig. 1 Global overview of aromatic SOA.…”
Section: Aromatic Hydrocarbon Emissionsmentioning
confidence: 95%
“…38 MAHs accounted for a substantial fraction of the total VOCs in urban and industrial areas. 39,40 Even in suburban regions, high concentrations of MAHs have been observed. 41 The implementation of control policies for VOCs has led to an overall decline in the annual average mass concentrations of MAHs in China from 2001 to 2016.…”
Section: Aromatic Hydrocarbon Emissionsmentioning
confidence: 99%
See 2 more Smart Citations